ASPEK VISIBILITY, LEGIBILITY, DAN READABILITY DALAM DESAIN PAPAN NAMA PURA KAHYANGAN KAJA DESA ADAT PANJER DENPASAR - Ni Kadek Yuni Utami; Ni Made Sri Wahyuni Trisna (Jurnal Lentera Widya, 2021)
The purpose of this report is to provide an explanation of the visibility, legibility and readability aspects in the design of the Kahyangan Kaja Temple sign board, Panjer Village, Denpasar. This report is part of the Community Service activities of the Bali Design and Business Institute in the manufacture of Environmental Facilities at Banjar Maniksaga, Panjer Village, Denpasar. The benefit of this report is that it pays attention to the condition of design facilities in public spaces, one of which is the Kahyangan Kaja Temple sign board which is owned by the people of Panjer Village as well as giving consideration in designing the public space sign board to the public. This report is carried out using a descriptive analysis method to describe the considerations of the visibility, legibility and readability aspects in terms of material selection, typography and placement in the design. With these considerations, it is hoped that the public will be more aware of the existence of the Kahyangan Temple and at the same time support the aesthetics of the Kahyangan Temple in Panjer Village, Denpasar, as well as provide an overview of the design aspects that support the optimization of the function of a nameplate in a public space. Keywords: signboard, design, material, placement, typography, Kahyangan Kaja Temple, Panjer Village